The effects of soft contact lens use on cornea and patient's recovery after autograft pterygium surgery. - Daglioglu, Mutlu Cihan; Coskun, Mesut; Ilhan, Nilufer; Tuzcu, Esra Ayhan; Ilhan, Ozgur; Keskin, Ugurcan; Ayintap, Emre; Oksuz, Huseyin (My University, 2014)
To investigate usage of soft contact lens (SCL) on post-operative pain relief and daily, activity due to pterygium surgery.

Autograft pterygium surgery was performed to 63 eyes of 63 patients. After surgery in 30, eyes of 30 patients in group-1, SCL was placed on the cornea. In 33 patients of group-2, antibiotic, pomade was applied and tightly covered with bandage. Follow-up visits were performed on 24th and, 48th h after the surgery. Re-epithelization time and pain scores were compared.

Patients' 24th h pain score was 2.96 ± 0.76 in group-1, and 4.15 ± 0.75 in group-2. The mean, pain score for 48 h was 1.66 ± 0.66 in group-1, and 2.96 ± 0.68 in group-2. Patients' pain scores for, both 24th h and 48th h were lower in group-1 (p<0.01). The mean re-epithelization times in, group 1 and 2 were 48 and 56.7h, respectively. Corneal re-epithelization is improved in patients, with SCL compared to group 2.

SCL seems effective on reducing post-operative pain and eye stinging, and may accelerate, corneal re-epithelization and maintaining daily activities.
Keywords: Pain; Pterygium; Soft contact lens; Surgery